3D Plastronics for Smartly Integrated Magnetic Resonance Imaging Coils - Gerges, Tony; Semet, Vincent; Lombard, Philippe; Gaillard, Sophie; Cabrera, Michel; Lambert, Simon Auguste (Frontiers in Physics, 2020)
Over the last four decades, Magnetic Resonance Imaging has become the gold standard imaging technique in many medical diagnoses for brain, cardiac and liver disease. However, due to low critical mass and great scientific challenges, instrumentation dedicated to preclinical MRI imaging has lagged behind instrumentation for clinical applications. The aim of this paper is to demonstrate that a set of new technologies such as the 3D Molded Interconnect Devices technology preferably named below as 3D Plastronics, 3D Printing and Microfluidics may be considered to provide a completely new way for designing preclinical MRI set-ups, i.e. the 3D prototyping and manufacturing of the MR coil, the sample holder and the peripherals, altogether. The fabricated MRI set-up can be used both for MRI of small biological samples and for in vivo imaging of a mouse brain. This work is the first step towards the full 3D manufacturing of tailor-made multifunctional MRI probes.